INTERTEXTUALITY IN ABDULLA ORIPOV’S POETRY - Xayrullayev Azamat (Galaxy International Interdisciplinary Research Journal, 2021)
The notion of intertextuality in artistic texts and its analysis are examined in this article using examples from Uzbek literature, specifically the types in Abdulla Oripov’s poetry. On the comprehension of the inertext and aesthetic text in the poem "Uzbekistan," scientific results were reached.